The production of canned lipote (Syzigium curanii) pie filling - Mar, Cherimae C. (2010)
This study focused on the production of canned pie filling using lipote (Syzigium curanii), a locally grown fruit tree that is indigenous to the Philippines. Two formulations of different amount of flour, 14g and 20g were tested and subjected to Forced Paired Preference Test to know which of these formulations was most preferred by the consumers. Using the Binomial Test as the statistical tool, it was determined that formulation B, with 20g of flour was significantly preferred over A, thus, making formulation B the final formulation for the product. The final product was then subjected to Acceptability Test and it was indicated through Sign Test, that the product was acceptable. The product's physicochemical properties, yeasts and molds count were also monitored from 0 hr to 504 hrs (3 weeks) The obtained data from monitoring the pH, TSS and TTA of the product were subjected to ANOVA Test and it was found out that the varying amounts were insignificantly different implying the stability of the product. Moreover, the pH and TSS of the product from 0 hr up to the 3rd week of storage remained within the USDA standard. In monitoring the yeasts and molds count, no microbial growth was observed. Based on the results, it concluded that the product is shelf stable.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2010
Keywords: Lipote; Forced Paired Preference Test; pH; Total Soluble Solids; Total Titratable Acid; ANOVA Test; Binomial Test; Sign Test; Pie filling; Canned pie filling; Shelf stable